Levantamiento del seno maxilar sin injerto óseo e implante simultáneo: un reporte de caso - Coronel Zabalbu, Brayam (2024)
A maxillary sinus lift was performed without bone grafting in a 23-year-old female patient who required the placement of a dental implant in the edentulous area of tooth 16. The clinical and tomographic evaluation made it possible to plan and perform the maxillary sinus lift using the transcrestal approach and without the need for bone grafting. The residual ridge of 6mm allowed the placement of a simultaneous dental implant. After 6 months of tomographic follow-up, before prosthetic loading, a vertical bone height of 8.83 mm was achieved, resulting in a vertical bone gain of 2.83 mm. Additionally, an adequate integration of the dental implant was observed without postoperative complications. Transcrestal sinus lift without the use of bone graft is shown to be a viable, safe and effective technique for the simultaneous placement of dental implants in patients with bone atrophy in the maxillary area. This technique offers advantages such as reduced surgical time, less morbidity, lower cost and a faster healing process compared to conventional methods.